Faculty-student interaction, School satisfaction, and Happiness among university students - Choi, Jihye (Opción, 2019)
This paper focuses on the relationship between university student’s interactions with faculty, school satisfaction, and happiness in Korea. The data were collected through a faculty-student interaction scale, school satisfaction scale, and happiness scale. Data analysis was conducted using SPSS 19. The study found that a structural equation modeling analysis showed good model fit indexes, directly and indirectly. To sum up the findings, there is clear evidence that positive faculty-student interaction directly predicts the happiness of university students, and indirectly predicts happiness via school satisfaction.